CARACTERIZACIÓN DE LOS TIPOS DE AZÚCARES PRESENTES EN EL ORITO (Musa acuminata), OBTENIDOS MEDIANTE HIDRODESTILACIÓN - ZAMBRANO BURGOS, DIANA MICHELLE (2025)
This research investigates the characterization of sugars present in orito (Musa acuminata), a banana variety with significant agro-industrial potential that is currently underutilized